2015
DOI: 10.1007/s12469-015-0111-x
|View full text |Cite
|
Sign up to set email alerts
|

Russian public transport system: the customers’ feedback on the service provision

Abstract: A considerable demand on gaining an inside knowledge on customers' perceptions of the service quality and subsequent complaint behavior in case of failure has defined the aim of this research paper. In this paper we analyse the pattern of customer complaint behavior in a widely used and widespread type of service-public transportation. Given the fact that the city of Kaliningrad is about to undergo a series of extensive qualitative improvements, driven by the federal investments allocated for major sporting an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
1
0
2
Order By: Relevance
“…Hasil penelitian Sumaedi, Mahatma, Bakti, & Yarmen (2012), Lierop & El-geneidy (2016), dan Yarmen & Sumaedi (2016) menunjukkan bahwa kualitas pelayanan mempunyai pengaruh terhadap minat penggunaan penumpang terhadap transportasi umum. Apabila service quality yang dirasakan konsumen jelek, maka akan mempengaruhi perilaku konsumen yang menimbulkan komplain sehingga berpengaruh terhadap behavior intentions (Mikhaylov, Gumenuk, & Mikhaylova, 2016). Berdasarkan berbagai hasil penelitian di atas, maka dibentuk hipotesa sebagai berikut: H1: Service quality mempunyai pengaruh positif terhadap behavioral intentions pada transportasi bus tarif premium.…”
Section: Pengembangan Hipotesisunclassified
“…Hasil penelitian Sumaedi, Mahatma, Bakti, & Yarmen (2012), Lierop & El-geneidy (2016), dan Yarmen & Sumaedi (2016) menunjukkan bahwa kualitas pelayanan mempunyai pengaruh terhadap minat penggunaan penumpang terhadap transportasi umum. Apabila service quality yang dirasakan konsumen jelek, maka akan mempengaruhi perilaku konsumen yang menimbulkan komplain sehingga berpengaruh terhadap behavior intentions (Mikhaylov, Gumenuk, & Mikhaylova, 2016). Berdasarkan berbagai hasil penelitian di atas, maka dibentuk hipotesa sebagai berikut: H1: Service quality mempunyai pengaruh positif terhadap behavioral intentions pada transportasi bus tarif premium.…”
Section: Pengembangan Hipotesisunclassified
“…Dell'Olio et al ( 2011) used a multinomial logit model to study the SQ as desired by the users. Using five attributes constituting of 29 bus quality indicators, Mahmoud et al (2012) derived user preferences by applying Analytical Hierarchy Process (AHP). It was found that different categories of users have different preferences towards bus service, and the study suggested putting more emphasis on analyzing the differential needs of each category to increase bus transit ridership.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Рассматривая железнодорожные вокзалы как современные многофункциональные комплексы, где реализуется широкий ассортимент товаров и предоставляется необходимый пакет основных и дополнительных услуг прибывающим, отправляющимся и транзитным пассажирам, в том числе при пересадке между железнодорожным и другими видами транспорта, важно отметить назревшую острую необходимость их адаптации к новым требованиям потребителей и рынка [Mikhaylov, Gumenuk, Mikhaylova, 2016]. В современных условиях организации пассажирских перевозок одной из основных задач становится повышение эффективности функционирования вокзальных комплексов.…”
Section: Introductionunclassified